Method of making syrup for cold drinks - Abdullayeva, Bufotima; Soliev, Muhammadjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article describes method how to get new syrup from local herbs. A description of the components that describe the functional properties of cool drinks is provided. The duration and quality of drinks were defined. Besides it is clear that the plants listed below may be useful in nature and can be used in medicine.